State-of-the-Art on Gender Equality in Cardiovascular Research - Cristina Rius; Andrea Sixto-Costoya; Rut Lucas-Domínguez; Juan Carlos Valderrama-Zurián (Women's Health Reports)
Objectives: Research in cardiac pathologies has historically been affected by gender bias in clinical manifestations, risk factors, and clinical trials, evidencing the fundamental need to integrate gender equality. The aim of this study is to analyze research on cardiovascular disease (CVD) and gender equality, starting from 2015 when the sustainable development goals (SDGs) were established. The U.S. National Institutes of Health also urged the inclusion of sex as a biological variable in the research that underpins it. Materials and Methods: International scientific production between 2015 and 2021 was evaluated using the Web of Science Citation Index-Expanded database, going deeper into the most prevalent pathophysiology and therapeutics that contribute to sex/gender-specific differences in cardiovascular (CV) research. Results: A total of 288 out of the 848,178 original articles in cardiology dealt with gender equality (CV-SDG-5), with the USA being the main contributor. In the CV publications that integrate gender equality, the main thematic category was “public, environmental, and occupational health.” The main pathologies highlighted were “hypertension,” “diabetes mellitus,” “stroke,” and “myocardial infarction,” and the predominant CV treatments were “hydroxymethylglutaryl-CoA reductase inhibitors” and “hypolipidemic agents.” Conclusions: Despite the efforts promoted by the 2030 Agenda and numerous public/private institutions promoting gender equality (SDG-5), only 0.03% of published CV research considers gender equality. This study highlights the importance of encouraging researchers to include sex and gender variables in their studies, and of increasing the commitment of public and/or private health research decision-makers to promote research that includes gender equality in its outcomes, in order to improve the diagnosis, treatment, and prognosis of CVD regardless of patient sex/gender.